Cardiac Care of Non-COVID-19 Patients During the SARS-CoV-2 Pandemic: The Pivotal Role of CCTA - Conte, Edoardo; Mushtaq, Saima; Mancini, Maria Elisabetta; Annoni, Andrea; Formenti, Alberto; Muscogiuri, Giuseppe; Gaudenzi Asinelli, Margherita; Gigante, Carlo; Collet, Carlos; Sonck, Jeroen; Guglielmo, Marco; Baggiano, Andrea; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims To evaluate the potential use of coronary CT angiography (CCTA) as the sole available non-invasive diagnostic technique for suspected CAD during COVID-19 pandemic causing limited access to hospital facilities Methods and Results A consecutive cohort of patients with suspected stable CAD and clinical indication to non-invasive test were enrolled in a hub hospital in Milan, Italy, from March 9th to April 30th 2020. Outcome measures were obtained as follows: cardiac death, ST-elevation myocardial infarction (STEMI), non-ST-elevation myocardial infarction (NSTEMI) and unstable angina. All changes in medical therapy following the result of CCTA were annotated. A total of 58 patients with a mean age of 64±11 years (36 male and 22 female) were enrolled. CCTA showed no CAD in 14 patients (24.1%), non-obstructive CAD in 30 (51.7%) and obstructive CAD in 14 (24.1%). ICA was considered deferrable in 48 (82.8%) patients. No clinical events were recorded after a mean follow-up of 376.4 ± 32.1days. Changes in medical therapy were significantly more prevalent in patients with vs. those without CAD at CCTA. Conclusion The results of the study confirm the capability of CCTA to safely deferring ICA in the majority of symptomatic patients and to correctly identifying those with critical coronary stenoses necessitating coronary revascularization. This characteristics could be really helpful especially when hospital resources are limited